2002
DOI: 10.1262/jrd.48.461
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Acrosomal Status and Motility in Rat Epididymal Spermatozoa Treated with .ALPHA.-Chlorohydrin for Predicting Their Fertilizing Capacity.

Abstract: Abstract. Rat cauda epididymal spermatozoa treated with α-chlorohydrin at concentrations of 0, 0.01, 0.1, and 1.0 under conditions that support in vitro fertilization were used to evaluate the effects of acrosomal status and sperm motility in predicting their fertilizing capacity. Acrosomal status was assessed by fluorescein isothiocyanate-conjugated concanavalin A (FITC-ConA) lectin assay in combination with supravital stain using calcein acetoxy methyl ester (CAM) and ethidium homodimer-1 (EthD-1) at 1, 3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It can be speculated, however, that this observation might be mediated through increased ROS production. Studies have, however, shown interesting links between decreased sperm activity, premature AR (Kato et al ., ) and reduced sperm motility as evidenced by increased total and progressive motility as well as VCL and ALH (Liu et al ., ). The premature initiation of acrosomal exocytosis seems to be related to perturbation of the plasma membrane stability.…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated, however, that this observation might be mediated through increased ROS production. Studies have, however, shown interesting links between decreased sperm activity, premature AR (Kato et al ., ) and reduced sperm motility as evidenced by increased total and progressive motility as well as VCL and ALH (Liu et al ., ). The premature initiation of acrosomal exocytosis seems to be related to perturbation of the plasma membrane stability.…”
Section: Discussionmentioning
confidence: 99%
“…Although, progressive motility is necessary for the spermatozoa to reach the oviductal ampulla, where is the site of fertilization (Kato et al, 2002 ), however, ghrelin did not aff ect signifi cantly the total and forward progressive movement in compared to the control group. It should be considered that there was an increase in the both sperm motility values in the ghrelin-treated rats than the control group on days 15 and 25 which were not statistically signifi cant.…”
Section: Discussionmentioning
confidence: 76%